As estratégias da imagem: as emergentes estéticas midiáticas entre o barroco e o pós modernismo - Dugnani, Patricio (2013)
This research aims to analyze visual media productions of images produced in postmodern contemporary times as well as to compare them to Baroque images in order to understand the similarities and differences that underpin the disruption or return of certain ways of expressing some kinds of contents that are present in the signic field of subjects in both periods. It is assumed that in both cases there are similar plastic actions, namely discursive processes of seeking references through intertextual processes from which result effects of parody and dispersion of signs to be taken as recurrent and common. The analysis of intertextual processes on the basis of signic redundancy theoretically relies on studies that encompass both Baroque and Postmodernism, such as those performed by Affonso Ávilla, Heinrich Wölfflin, Arnold Hauser, and Frei Pedro Sinzig regarding the first field of knowledge. Jean-François Lyotard, Stuart Hall, David Harvey, Linda Hutcheon, and Terry Eagleton are for the second one. Intertextuality, the main concept that reveals the process that approximates the image formation in both periods, will be based on studies of Roland Barthes. According to him a text, not necessarily verbal, is made of multiple writings from several cultures that are in dialogue. In order to contemplate the objective of this study the research corpus is purposely hybrid and it comprises Baroque works of art such as painting and tiling, plus films, music videos, and advertisements of Postmodernism period. This choice is mainly because an image is considered like a system of signs that express contents, thus becoming a support and mean of communication, as well as an example of media. The relevance of the work relates to the importance of Baroque images to build an important chapter of Brazilian cultures and the relative scarcity of comparative analysis between both periods, especially in our context